2019
DOI: 10.1155/2019/2510936
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyl Ditelluride: Redox-Modulating and Antiproliferative Properties

Abstract: Tellurium is a rare element that has been regarded as a toxic, nonessential element, and its biological role is not clearly established. In addition, the biological effects of elemental tellurium and some of its organic and inorganic derivatives have been studied, leading to a set of interesting and promising applications. Diphenyl ditelluride (DPDT), an organic tellurium derivate, showed antioxidant, antigenotoxic, antimutagenic, and anticancer properties. The antioxidant and prooxidant properties of DPDT are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 86 publications
2
5
0
1
Order By: Relevance
“… 48 Selenium plays an important role in the cell cycle and apoptosis, but these mechanisms are extremely complex and have not yet been fully elucidated. 54 As for tellurium, studies evaluating its biological activity are still scarce, although antineoplastic effects from tellurium compounds are believed to be associated with ROS formation, cell cycle arrest, induction of programmed cell death, and may have immunomodulatory effects, 55 being a class of compounds with great potential to be explored for the development of new anticancer molecules. 56 In this work, we could observe biological activity from all synthesized chalcogen-naphthoquinones derived from both diorganoyl diselenides and diorganoyl ditellurides, with an impact on cell migration, proliferation, and overall survival in OSSC cells.…”
Section: Resultsmentioning
confidence: 99%
“… 48 Selenium plays an important role in the cell cycle and apoptosis, but these mechanisms are extremely complex and have not yet been fully elucidated. 54 As for tellurium, studies evaluating its biological activity are still scarce, although antineoplastic effects from tellurium compounds are believed to be associated with ROS formation, cell cycle arrest, induction of programmed cell death, and may have immunomodulatory effects, 55 being a class of compounds with great potential to be explored for the development of new anticancer molecules. 56 In this work, we could observe biological activity from all synthesized chalcogen-naphthoquinones derived from both diorganoyl diselenides and diorganoyl ditellurides, with an impact on cell migration, proliferation, and overall survival in OSSC cells.…”
Section: Resultsmentioning
confidence: 99%
“…The use of those drugs is however limited due to the emergence of resistance which requires novel approaches to overcome the underlying mechanisms [ 28 , 29 ]. In that sense, the cytotoxic potential of DPDT has been previously evaluated against several tumor cell models, such as CRC, gliomas, melanoma and promyelocytic leukemia cancer cells [ 22 ]. This compound was suggested to act as a putative TOP1 inhibitor in in vitro studies as well as in yeast models [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This compound was suggested to act as a putative TOP1 inhibitor in in vitro studies as well as in yeast models [ 20 ]. Several studies also reported genotoxic, mutagenic and pro-oxidant properties of DPDT in different biological models [ 22 , 25 ]. However, its precise mechanism of action against tumor cells has been to date poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the incorporation of Te into proteins and the possible biological role of chalcogenide metal nano-crystals derived from amino acid- and protein-bound Te forms, analogous to those of other sulfur-binding elements [ 77 , 103 , 104 , 105 , 106 ]. Organo-tellurium compounds have antioxidative, protective, or antiproliferative attributes in the cell system [ 107 , 108 , 109 ]. These organic Te compounds include hydroxyphenyl-telluride, aminophenyl-telluride, carboxyphenyl-telluride [ 107 ], diphenyl ditelluride [ 110 ], and thiophene-based organo-tellurium [ 109 ].…”
Section: Toxicity Of Tellurium and Nano-telluriummentioning
confidence: 99%